Metabolic Effects of Avocado/Soy Unsaponifiables on Articular Chondrocytes - Lippiello, Louis (Oxford University Press, 2008)
Avocado/soy unsaponifiable (ASU) components are reported to have a chondroprotective effect by virtue of anti-inflammatory and proanabolic effects on articular chondrocytes. The identity of the active component(s) remains unknown. In general, sterols, the major component of unsaponifiable plant material have been demonstrated to be anti-inflammatory in vitro and in animal models. These studies were designed to clarify whether the sterol content of ASU preparations were the primary contributors to biological activity in articular chondrocytes. ASU samples were analyzed by high pressure liquid chromatography (HPLC) and GC mass spectrometry. The sterol content was normalized between diverse samples prior to in vitro testing on bovine chondrocytes. Anabolic activity was monitored by uptake of 35-sulfate into proteoglycans and quantitation of labeled hydroxyproline and proline content after incubation with labeled proline. Anti-inflammatory activity was assayed by measuring reduction of interleukin-1 (IL-1)-induced synthesis of PGE2 and metalloproteases and release of label from tissue prelabeled with S-35.All ASU samples exerted a similar time-dependent up-regulation of 35-sulfate uptake in bovine cells reaching a maximum of greater than 100% after 72 h at sterol doses of 1–10 μg/ml. Non-collagenous protein (NCP) and collagen synthesis were similarly up-regulated. All ASU were equally effective in dose dependently inhibiting IL-1-induced MMP-3 activity (23–37%), labeled sulfate release (15–23%) and PGE2 synthesis (45–58%). Up-regulation of glycosaminoglycan and collagen synthesis and reduction of IL-1 effects in cartilage are consistent with chondroprotective activity. The similarity of activity of ASU from diverse sources when tested at equal sterol levels suggests sterols are important for biologic effects in articular chondrocytes.